Pengaruh Keaktifan Berorganisasi sebagai Pengurus IPM terhadap Prestasi Belajar Peserta Didik di MTs Muhammadiyah 1 Natar - Sutiono; Syaiful Anwar; Mujib (Attractive : Innovative Education Journal, 2024)
The participation and activity of students in the IPM organization which is very busy with various activities definitely takes up a lot of their free time and rest time. If it is related to students' activeness in extracurricular activities or organizations, students who are active in organizations have relatively little time to study compared to students who do not join organizations, for students who are not active in organizations they have enough time to study and help them to be able to follow lessons well so that you can get high results. Based on this orientation, it can be concluded that organizational activity as an IPM administrator has a role in improving student learning achievement at MTs Muhammadiyah 1 Natar, South Lampung. Therefore, this research aims to determine the influence of organizational activity as an IPM administrator on student learning achievement. Quantitative Research is the approach the author uses for this research. The variables used are organizational activity as an IPM administrator and learning achievement. The population in the research was 21 students as administrators of IPM MTs Muhammadiyah 1 Natar South Lampung. Questionnaire techniques and interview techniques are the main data for this research, supported by documentation techniques, the data of which is then used to support the credibility of this research. From the results of the research that has been carried out, it was found that the influence of organizational activity as an IPM administrator on the learning achievement of students with an F gradecount 11.103 and a significance of 0.004. There is a positive influence of organizational activity as an IPM administrator on the learning achievement of class IX students at MTs Muhammadiyah 1 Natar Lampung Selatan with a value of tcount  3.332 and t table 3.883 with a significant value of 0.004. Keywords:  Students’ Learning Achievement, Organizational Activeness